Neutron Therapy for High‐Grade Salivary Carcinomas in the Adjuvant and Primary Treatment Setting. (30th June 2020) - Cash, Harrison; Harbison, R. Alex; Futran, Neal; Parvathaneni, Upendra; Laramore, George E.; Liao, Jay; Cannon, Richard; Rodriguez, Cristina; Houlton, Jeffrey J.
Abstract : Objectives/Hypothesis: Our primary objective was to compare differences in survival of patients with high‐grade salivary gland carcinomas (SGCs) receiving adjuvant neutron versus photon radiotherapy using a hospital‐based national cohort and restricted mean survival time (RMST) analysis. Our secondary objective was to compare survival of similar patients treated with primary neutron versus photon radiation. Study Design: Multicenter, retrospective population‐based study of patients within the National Cancer Database from 2004 to 2014. Methods: One thousand eight hundred forty‐four patients were selected on diagnosis of high‐grade parotid and submandibular malignancies. One thousand seven hundred seventy‐seven patients receiving photon and 67 patients receiving neutron therapy were identified who met inclusion criteria. Patients were then categorized as having primary surgery with adjuvant radiation or primary radiation without prior surgery. Bivariate analysis was performed to assess for differences between groups, and RMST analysis was performed at 1‐, 2‐, and 5‐year timepoints with controlling for available covariate data. Results: There was no significant difference in RMST for patients receiving neutrons over photons at 1, 2, and 5 years in the adjuvant setting. Among patients undergoing primary radiotherapy, there was a difference in RMST of 2.29 months at 1 year and 5.05 months at 2 years for neutrons over photons, though this benefit was not observed at 5 years post‐therapy. Conclusions: For patients with high grade SGCs undergoing adjuvant photon versus neutron radiotherapy, there was no difference in RMST. There was observed to be a significant difference in RMST at 1 and 2 years among patients undergoing primary neutron therapy of up to 5 months. Given the benefit observed with primary neutron therapy, it should be considered in both the primary and adjuvant treatment setting. Level of Evidence: 4 Laryngoscope, 131:541–547, 2021